The Role of Managers' Cognitive Styles in Achieving Organizational Ambidexterity - Kased.M.Al-Assadi *, Adel; Ali Mhaibes , Hussam (Journal of Economics and Administrative Sciences, 2024)
the study aims to ascertain how approaches contribute to the Ministry of Planning's organizational ambidexterity. To complete the conclusions, it also seeks to ascertain the factors and dimensions of the study, get the results, and interpret them. The recommendations illustrate how companies may modify and enhance their behavior while utilizing these factors in the field. The descriptive-analytical technique is used to ensure the maximum level of accuracy possible in the conclusions and suggestions. General managers, several department directors, and division supervisors constituted the research sample. The primary instrument used in the research was a questionnaire distributed to the target sample of 105 respondents. The comprehensive inventory method was also employed, and multiple statistical programs, including PLS SMART V3.6 and 28 SPSS V., were utilized to complete, analyze, and test the research's questions and hypotheses. The research results showed a statistically significant effect. Cognitive styles affect organizational ambidexterity, either directly or through the degree of their dimensions. There is also a positive correlation between the dimensions of cognitive styles, their dimensions (cognitive style, planning style, creative style, collaborative style), and organizational ambidexterity.Paper type: Research paper.